INCREASING STUDENTS’ READING COMPREHENSION THROUGH PICTURE - Dahlia M Said (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: This research aimed to increase students’ reading comprehension through picture. This research answers there main questions (1) How is the improvement of the students’ reading comprehension in descriptive text using pictures? Twenty two students of the eighth grade students of SMPN SATU ATAP EKOREKO were instructed through Picture media to increase their reading comprehension. The methodology of this research used Classroom Action Research (CAR). The research instrument is reading test. This study was conducted in two cycles. Each cycle consists of planning, action, observation and reflection. The researcher found an improvement of students’ reading comprehension by using picture media. It can be seen in the score of preliminary test in first cycle nine % students got score above 75 with the average score 67.63. The students did not achieve the criteria of success. Then, the researcher continued to the second cycle, this action that shows improvement. It can be seen in final-test, nineteen % students got score above 75 with the average score 85.45. It can be concluded that picture can increase students’ reading comprehension.Key Words: Reading Comprehension, Picture, Descriptive text.